The Three Waves of the Charismatic Renewal in Réunion Island: Interactions with Local Religious and Cultural Practices. (9th September 2020) - Aubourg, Valerie
Abstract : In Réunion Island, the Charismatic Renewal was introduced in 1974 by the Mauritian nun Marie-Lise Corson. It quickly became extremely successful against the Assemblies of God, a Pentecostal movement which had established itself on the island eight years earlier. And just like this other movement, it drew heavily on the "Creole religious system" in order to foster a seemingly reverse process of "eradicating" popular religiosity. It redefined the traditional system without discrediting it. Beginning with the 1980s-1990s, growing religious globalization encouraged new communities originally set up in mainland France or Quebec to come to the island. The life of these outside groups intersected with that of the local assemblies and leaders, winning them over. This second period further corresponded to a normalization of the Renewal which brought its practices back into the Catholic fold. A third phase started in the late 1990s and early 2000s with the creation of groups on the fringes of the diocesan Renewal that tended to re-emphasize the attributes of Creole identity and move closer to the neo-Pentecostal movement. Thus, the study of the birth and development of the Charismatic Renewal in the French Indian Ocean département brings to light three waves. Drawing on ethnological research, this paper will analyse them by looking at the ways in which this transnational and transdenominational movement has interacted with local religious and cultural practices.